Teaching Theory of Programming: Methodology and Basic Notions - Nikitchenko, M.C. (Journal of Information Technologies in Education (ITE), 2008)
An idea of including into computing curricula an integral course “Theory of Programming” is proposed. Its main methodological aspects and basic notions are discussed. Such an approach leads to a simple structure of the course, its integrity with such programming related courses as mathematical logic and computability theory.